Особенности измерения обмена кальция у крыс при переломе малоберцовой кости в зависимости от применяемых лечебных факторов = Features measurement of calcium exchange in rats in fractures of the fibula depending on applied medical factors - K. V. Pаvlеnkо; A. I. Gоzhеnkо; B. A. Nаsibullin; E. B. Uvarоvа (Kazimierz Wielki University, 2015)
Pаvlеnkо К. V., Gоzhеnkо А. I., Nаsibullin B. А., Uvarоvа Е. B. Особенности измерения обмена кальция у крыс при переломе малоберцовой кости в зависимости от применяемых лечебных факторов = Features measurement of calcium exchange in rats in fractures of the fibula depending on applied medical factors. Journal of Education, Health and Sport. 2015;5(11):727-734. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.46669 http://ojs.ukw.edu.pl/index.php/johs/article/view/3404 http://pbn.nauka.gov.pl/works/717178   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   УДК 616.718.6-001.5-085.814.5   Особенности измерения обмена кальция у крыс при переломе малоберцовой кости в зависимости от применяемых лечебных факторов   К. В. Павленко, А. И. Гоженко, Б. А. Насибуллин, Е. Б. Уварова   ГП «Украинский НИИ медицины транспорта» МЗ Украины, Одесса            РЕЗЮМЕ Авторы, по результатам экспериментальных исследований проведенных на 90 крысах о изменениях показателей кальциевого обмена при переломе малой берцовой кости, установили: что эти изменения носят фазный характер. Этапы изменения показателей кальциевого обмена совпадают с фазами репаративного процесса в области перелома. Применение «Апизартрона» сохраняет фазность изменений, но ускоряет переход между ними. При применении плазмы обогащенной тромбоцитами наблюдается практическое отсутствие фазы воспаления, а протяженность остальных фаз репарации резко сокращается. Авторы полагают, что экзогенное введение факторов роста с плазмы обогащенной тромбоцитами активирует процессы образования тканеспецифических элементов и структурно-функциональной организации костной ткани.   Ключевые слова: кальций, щелочная фосфатаза, «Апизартрон», плазма обогащенная тромбоцитами.   FEATURES MEASUREMENT OF CALCIUM EXCHANGE IN RATS in fractures of the fibula depending on applied medical factors   К. V. Pаvlеnkо, А. I. Gоzhеnkо, B. А. Nаsibullin, Е. B. Uvarоvа   Ukrainian Scientific and Research Institute of Transport Medicine, Odessa, Ukraine            Abstract                                                                      There was an experimental study on 90 rats. The authors stated that in case of fracture of fabula variation of calcium metabolism indices has a phasic habit. Variation milestones are the same as the phases of reparative process in the fracture. The usage of "Apizartron" maintains variation phasicity but promotes transaction in between. In applying the platelet-rich plasma the inflammation phase is almost absent and the extension of other repair phases slashes. The authors consider that exogenic intake of growth promoting substance from the platelet-rich plasma promotes the building-up process of tissue-specific features and structural-functional organization of osseous tissue.              Key words: calcium, alkaline phosphatases, "Apizartron", platelet-rich plasma.